Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Inspektorat Daerah Provinsi Sulawesi Utara - Priskila Trifena Barias; Tonny Maringka; Farly Teneh (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance at the Regional Inspectorate Office of North Sulawesi Province. The research uses a quantitative method with a survey approach, where data were collected through questionnaires distributed to 50 respondents. The analysis techniques employed include validity, reliability, normality, heteroscedasticity, multicollinearity tests, and multiple linear regression. The results of the analysis indicate that motivation and work discipline have a significant positive effect on employee performance. The regression test shows that the coefficient of determination (R²) is 73.4%, which means that motivation and work discipline contribute 73.4% to employee performance, while the remaining percentage is influenced by other factors not studied. The F-test value of 64.750 with a significance level of 0.000 indicates that the regression model, which includes motivation and work discipline, is overall significant in explaining variations in employee performance. This study provides insights that improving motivation and work discipline can significantly enhance employee performance. These findings can be used by management to formulate more effective policies to improve employee performance and contribute to the academic literature in the field of human resource management.